Analysis of vicilin (7S)-class globulin in cocoa cotyledons from various genetic origins - Amin, I.; S., Jinap; B., Jamilah; Harikrisna, K.; Biehl, B. (Society of Chemical Industry (SCI), 2002)
Cocoa cotyledons contain vicilin (7S)-class globulin (VCG), a major storage protein. It is the native source of oligopeptides and free amino acids which have been identified as precursors of cocoa-specific aroma and are formed through proteolysis during fermentation. High-resolution electrophoresis of native proteins isolated from ripe, unfermented cocoa cotyledons harvested from different cultivars was used to determine genetic differences of the genotypes. Flavour differences have been reported to exist after standard fermentation in cocoa beans harvested from various genotypes. In this paper, SDS-PAGE and 2D IEF/SDS-PAGE polypeptide separation patterns are shown which were separately isolated from cotyledons of various genetic origins. Cotyledons from three cultivars belonging to genetically distant varieties and a hybrid, Criollo, Forastero and Trinitario, did not reveal any analytical identity differences of VCG subunit polypeptide bands. Additionally, proteins of cotyledons harvested from three of those clones which were reported to produce genotype-specific flavour differences in raw cocoa after standard fermentation, SCA 12, UIT1 and PBC 140, when analysed in the same way, did not indicate differences. Thus the cotyledon storage proteins from various genetically different cocoa trees are, within methodological limits, the same. We conclude that aroma differences in raw cocoa harvested from various genotypes are the result of other genetic, physiological or curing-related factors, but are not due to genetic differences of aroma precursors derived from storage proteins. © 2002 Society of Chemical Industry.